Georgia : Request for Stand-By Arrangement; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Georgia. (IMF Staff Country Reports; Country Report ;, 2008)
This paper examines Georgia's request for an 18-month arrangement for SDR 477.1 million, equivalent to about USD 750 million, which would constitute exceptional access. IMF support to the government's macroeconomic policies is intended to provide the needed financing to rebuild gross international reserves, and to help restore investor confidence. Monetary policy has to tackle the dilemma of providing sufficient liquidity to the banking system while stabilizing the exchange rate and avoiding an excessive loss of international reserves.